2021
DOI: 10.1039/d1sc05072a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a heterobimetallic actinide nitride and an analysis of its bonding

Abstract: The heterobimetallic actinide nitride [(NR2)3UV(μ-N)ThIV(NR2)3] (R = SiMe3) has an mJ = 5/2 ground state and its highest energy 5f excited state is primarily 5f-Nnitride σ-antibonding in character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…More recently, Liddle and co-workers analyzed the optical and EPR spectra of the C 3v -symmetric U­(V) nitride, [U V (Tren TIPS )­(N)] − (Tren TIPS = N (CH 2 CH 2 N Si i Pr 3 ) 3 ), and extracted the corresponding crystal field splitting parameters . We subsequently performed a similar analysis on the bridged-nitride complex, [(NR 2 ) 3 U V (μ-N)­Th IV (NR 2 ) 3 ] (R = SiMe 3 ), which also features C 3v -symmetry . These studies demonstrated that, for both complexes, the U–N nitride interaction strongly destabilizes the f σ orbital and (to a lesser extent) the f π orbitals.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Liddle and co-workers analyzed the optical and EPR spectra of the C 3v -symmetric U­(V) nitride, [U V (Tren TIPS )­(N)] − (Tren TIPS = N (CH 2 CH 2 N Si i Pr 3 ) 3 ), and extracted the corresponding crystal field splitting parameters . We subsequently performed a similar analysis on the bridged-nitride complex, [(NR 2 ) 3 U V (μ-N)­Th IV (NR 2 ) 3 ] (R = SiMe 3 ), which also features C 3v -symmetry . These studies demonstrated that, for both complexes, the U–N nitride interaction strongly destabilizes the f σ orbital and (to a lesser extent) the f π orbitals.…”
Section: Introductionmentioning
confidence: 99%
“…(bottom) Calculated weight percent for all reported heterometallic An-MOFs and heterometallic An-molecular complexes as a function of structural 1/d (d = density). [1][2][3][4][5][6][7][8][9][10][11] presence of the thorium salt under an inert atmosphere using oxygen-free solvent), while transmetallation was rapidly completed in air. Interestingly, all attempts to use Th-MOFs as a precursor for uranium integration using the same method and experimental conditions were completely unsuccessful as confirmed by ICP-MS.…”
Section: Resultsmentioning
confidence: 99%
“… ( top ) A schematic representation of changes in properties of heterometallic actinide‐containing MOFs as a function of degree of transmetallation from U (purple) to Th (red) and Pu (yellow). ( bottom ) Calculated weight percent for all reported heterometallic An‐MOFs and heterometallic An‐molecular complexes as a function of structural 1/ d ( d =density) [1–11] …”
Section: Introductionmentioning
confidence: 99%
“…Reactions of uranium complexes with azides and oxygen-transfer reagents have been heavily studied due to interest in actinide-ligand multiple bonding. [1][2][3][4][5][6] Additionally, uranium oxo and imido species are of interest for theoretical and reactivity studies. [7][8][9][10][11][12][13] To generate uranium-nitrogen multiple bonds, often a uranium complex is reacted with an organic azide reagent, RN 3 , or azobenzene, PhNvNPh, to oxidize the metal center and install an NR imido ligand or NPh.…”
Section: Introductionmentioning
confidence: 99%